2005
DOI: 10.1111/j.1399-0039.2005.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel HLA‐A*0278 allele in a Chinese family*

Abstract: A novel human leukocyte antigen-A (HLA-A) allele, A*0278, has been identified in a Chinese family using DNA-based typing and molecular cloning methods. The alleles A*0278 differs from its closest matching HLA sequence of A*0256 by a silent substitution at 102 A > C and by two replacement substitutions, 98T > A and 292 C > G in exon 2, resulting in a change of codon 33 from Phe (TTC) to Tyr (TAC) and codon 98 from His (CAC) to Asp (GAC). Serology study revealed that A*0278 is associated with HLA-A2 broad specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…In summary, it is suggested that HLA-A*9203 is the result of a gene conversion between A*0207 and A*1101/ 02 or A*0301, where a putative conversion fragments was localized in nucleotide region 240 -282 of exon 2. Similarly, A*0256, A*0262 and A*0278 (Ji et al, 2005) (Fig. 1a) are also the result of a gene conversion where a nucleotide motif, most likely from A3 or A11, is exchanged with the homologous region of an A*020101 or 0206 backbone.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, it is suggested that HLA-A*9203 is the result of a gene conversion between A*0207 and A*1101/ 02 or A*0301, where a putative conversion fragments was localized in nucleotide region 240 -282 of exon 2. Similarly, A*0256, A*0262 and A*0278 (Ji et al, 2005) (Fig. 1a) are also the result of a gene conversion where a nucleotide motif, most likely from A3 or A11, is exchanged with the homologous region of an A*020101 or 0206 backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Although the serological specificity of A*02:78 is reported to be A2, ANN placed A*02:78 in A69, A2 and A3. Allele A*02:78 reportedly reacts with anti‐A2 + A28 and anti‐A2 + A69 antisera but not with anti‐A2 or ‐A69 serum alone (Ji et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[10] Each 25 μl PCR reaction mixture contained 250 ng of DNA, 0.2 mmol/L of dNTPs, 2 units of Taq DNA polymerase (Dream Taq TM DNA polymerase, Fermentas), 3.5 mmol/L of MgCl 2, and primer sets at different concentrations [Table 1]. A pair of nucleotides was used to generate a 429 pb PCR fragment from the human growth hormone gene [Table 1][11] which was included as an internal control to avoid false negative results. Amplification was performed in a thermocycler (Gene Amp ® PCR System 9700).…”
Section: Methodsmentioning
confidence: 99%
“…Specific primers were Rh223vf and primer ga51 for T223V [Table 2][14] generating a 164 pb. To avoid false negative results, an internal control amplifying the human growth hormone gene (429 pb) [Table 1][11] was included. Amplifications were carried out with Taq (Invitrogen) in a final volume of 10 μl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation